First International Workshop on Software Engineering for Pervasive Computing Applications, Systems, and Environments (SEPCASE ' 2007
DOI: 10.1109/sepcase.2007.6
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Role of Software Architecture in Dynamic and Fault Tolerant Pervasive Systems

Abstract: Pervasive systems are rapidly growing in size, complexity, distribution, and heterogeneity. As a result, the traditional practice of developing one-off embedded applications that are often rigid and unmanageable is no longer acceptable. This is particularly evident in a growing class of mobile and dynamic pervasive systems that are highly unpredictable, and thus require flexible and adaptable software support. At the same time, many of these applications are mission critical and have stringent fault tolerance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…Architecture plays a key role in pervasive fault tolerance systems [12]. With respect to wearable computing in healthcare, two common architectures are used which are explained as follows.…”
Section: Related Workmentioning
confidence: 99%
“…Architecture plays a key role in pervasive fault tolerance systems [12]. With respect to wearable computing in healthcare, two common architectures are used which are explained as follows.…”
Section: Related Workmentioning
confidence: 99%
“…In Fig. 4(e), 1,2 DA that has flag 1 is selected to system redeploy. The selected component is still DA are also pruned.…”
Section: A*_d Algorithmmentioning
confidence: 99%
“…Possible reasons include: increase in the speed and capacity of hardware, the emergence of wireless ad hoc networks, proliferation of sensors, and handheld computing devices, and so on. A number of researches have shown that a promising approach to resolve the challenges is to employ the principles of software architectures [1] . Software Architecture (SA) is a collection of models that capture software system principle design decisions in the form of components (location of 1 system computation and data management), connectors (location of component interaction), and configurations (specific arrangements of components and connectors intended to solve specific problems) [2] .…”
Section: Introductionmentioning
confidence: 99%
“…Seo et al have argued that an effective way to ensure fault tolerance in complex software systems is to employ the principles of software architectures [20]. They also argue that the complexity of pervasive software systems creates challenges in maintaining the desired fault tolerance properties and that software architectures, in some way, can help create an abstraction barrier between the functional properties of a software system and the fault tolerance ensuring components.…”
Section: Fault and Adversary Tolerancementioning
confidence: 99%